2014
DOI: 10.5152/tpd.2014.3355
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Anti-Toxoplasma gondii Antibody Distribution and Risk Factors Among Pregnant Women Admitted to Obstetrics Polyclinic of Canakkale Onsekiz Mart University Hospital

Abstract: We found that Toxoplasma IgG antibody seropositivity (28.8%) was similar to that found in the other studies from western Turkey.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 17 publications
1
3
0
5
Order By: Relevance
“…The seropositivity rates of T. gondii (36.9%, 33.9%, and 28.8%) in other studies performed in different geographical regions of our country were found to be higher than those in our results. [7][8][9] The results were similar in every study conducted in Turkey. When we checked other countries, the seropositivity rates of T. gondii were 7% in Norway, 10% in the United Kingdom, 19% in Italy, 29.9 in Sri Lanka, [10] 31.7% in Thailand-Myanmar, [11] 32% in Spain, 33% in Austria, 34% in Slovenia, 44% in France, [12] 46.2% in Yemen, [13] and 82.6% in Lebanon.…”
Section: Discussionsupporting
confidence: 63%
“…The seropositivity rates of T. gondii (36.9%, 33.9%, and 28.8%) in other studies performed in different geographical regions of our country were found to be higher than those in our results. [7][8][9] The results were similar in every study conducted in Turkey. When we checked other countries, the seropositivity rates of T. gondii were 7% in Norway, 10% in the United Kingdom, 19% in Italy, 29.9 in Sri Lanka, [10] 31.7% in Thailand-Myanmar, [11] 32% in Spain, 33% in Austria, 34% in Slovenia, 44% in France, [12] 46.2% in Yemen, [13] and 82.6% in Lebanon.…”
Section: Discussionsupporting
confidence: 63%
“…In keeping with this, only consumption of contaminated goat milk was associated with occurrence of human acute toxoplasmosis [42][43][44].Nevertheless, some sero-epidemiological surveys specified significantly association with ingestion of raw milk of other livestock and T. gondii infection [45][46][47][48][49]. Association amid raw milk ingestion and T. gondii transmission to human has been conveyed from Iran [11], USA [7], Turkey [50]Germany [51] and Mexico [45]. Other works conducted on Jordan [52] and Kyrgyzstan [16] specified non-significant effect of dairy consumption and occurrence of toxoplasmosis.…”
Section: Discussionmentioning
confidence: 94%
“…As in many countries, studies in Turkey are continuing. There are studies on seroprevalence of toxoplasmosis and schizophrenia reported from the University and State Hospital in our research area Canakkale [105][106][107][108].…”
Section: Toxoplasmosis and Pregnancymentioning
confidence: 99%